PENERAPAN TERAPI GENGGAM BOLA KARET DAN LATIHAN RANGE OF MOTION PASIF PADA LANSIA PASCA STROKE DENGAN GANGGUAN MOBILITAS FISIK: SEBUAH LAPORAN KASUS - Adinda Zahira Dwinaputri; Raini Diah Susanti; Sheizi Prista Sari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stroke is one of the leading causes of long-term disability and mortality worldwide, with a common consequence being muscle weakness (hemiparesis) that results in impaired mobility and decreased independence among older adults. Non-pharmacological rehabilitation efforts, such as rubber ball gripping therapy, can serve as a simple alternative intervention to improve muscle strength and motor function. This case study aimed to determine the effect of rubber ball gripping therapy and range of motion (ROM) exercises on improving muscle strength in an elderly post-stroke patient at UPTD Griya Lansia Ciparay. The subject was a 68-year-old male elderly patient with left-sided hemiparesis following a stroke. The intervention was conducted for six consecutive days, consisting of rubber ball gripping exercises for 10–15 minutes daily, and muscle strength was evaluated using the Manual Muscle Testing (MMT) method. The results demonstrated an improvement in left extremity muscle strength from 2/5 to 4/5, accompanied by increased motivation and self-confidence in the patient. Rubber ball gripping therapy combined with range of motion exercises proved effective in enhancing muscle strength in elderly post-stroke patients. This intervention aligns with the objectives of the Sustainable Development Goals (SDGs), particularly Goal 3: Good Health and Well-being, which emphasizes the importance of improving quality of life and achieving optimal health for all age groups, including older adults.